Muṭālaʻāt-i fiqh va ḥuqūq-i Islāmī : dū faṣlnāmah-i ʻilmī, pizhūhishī - Dānishgāh-i Simnān (Dānishgāh-i Simnān, 2010)
Studies in islamic law and jurisprudence with special reference to Iran.
Keywords: Islamic law : Periodicals; Islamic law : Iran : Periodicals; Islamic law; Iran